Single-digit-micrometer thickness wood speaker - Wentao Gan (Nature Portfolio, 2019)
Thin films of several microns in thickness are ubiquitously used in packaging, electronics, and acoustic sensors. Here the authors demonstrate an ultrathin wood film with an aligned and laminal structure and acoustic properties which allows application of the film as diaphragm for an audio speaker.